Praziquantel use in aquaculture – Current status and emerging issues. (April 2022) - Norbury, Luke J.; Shirakashi, Sho; Power, Cecilia; Nowak, Barbara F.; Bott, Nathan J.
Abstract: Parasitic diseases are major constraints in fish mariculture. The anthelmintic praziquantel (PZQ) can effectively treat a range of flatworm parasites in a variety of fish species and has potential for broader application than its current use in the global aquaculture industry. In this review we report on PZQ's current use in the aquaculture industry and discuss its efficacy against various flatworm parasites of fish. Routes of PZQ administration are evaluated, along with issues related to palatability, pharmacokinetics and toxicity in fish, while PZQ's effects on non-target species, environmental impacts, and the development of drug-resistance are discussed. Graphical abstract: Image 1